2012
DOI: 10.2174/1874279301206010046
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Infections in Adult Patients with Haematological Malignancies

Abstract: Abstract:Patients with haematological malignancies are at increased risk of infections not only because of the malignancy itself but also because of neutropenia induced by intensive chemotherapeutic treatment, and the cytotoxic effect on the cells that line the alimentary tract. In haematological malignancy patients with a compromised inflammatory response, the classic signs and symptoms of infection may be masked. The results of blood cultures therefore play an important diagnostic role. Bacteraemia is a rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…18 Similar data were reported by Lv et al from China showing 73-100% of MRCNS strains. 19 In general, literature data most often show the prevalence of Gram-positive over Gram-negative bacteria among blood isolates, 17,[20][21][22][23] which is in line with the results of our own research conducted from 2011 to 2014 (63-70% vs 30-40%). The previous study from 2001-2002 from the same clinic showed a greater number of Gram-negative than Gram-positive bacteria (56% vs 44%) isolated from blood.…”
Section: Discussionsupporting
confidence: 86%
“…18 Similar data were reported by Lv et al from China showing 73-100% of MRCNS strains. 19 In general, literature data most often show the prevalence of Gram-positive over Gram-negative bacteria among blood isolates, 17,[20][21][22][23] which is in line with the results of our own research conducted from 2011 to 2014 (63-70% vs 30-40%). The previous study from 2001-2002 from the same clinic showed a greater number of Gram-negative than Gram-positive bacteria (56% vs 44%) isolated from blood.…”
Section: Discussionsupporting
confidence: 86%
“…These findings are similar to other studies, which have found that individuals with various cancer types prefer receiving information that is tailored to their specific characteristics [36,37]. The provision of tailored information is however particularly important for individuals with haematological cancers, as each individual's risk of infection is highly variable and influenced by multiple factors, including type of cancer and treatments received [14]. Providing survivors with generic information is therefore unlikely to help survivors make informed decisions about the changes they should personally make, and instead may result in confusion.…”
Section: The Type Of Information and Support Wanted By Haematologicalsupporting
confidence: 88%
“…In addition, many of the treatments used with haematological cancers, including bone marrow transplant, chemotherapy and monoclonal antibodies, lead to immunodeficiency [12,11]. Consequently, many haematological cancer survivors are at increased risk of developing infections [13][14][15], which often carry extensive morbidities and in many cases lead to death [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In a case-control study by Pagano et al, risk factors for bacteremia in patients with hematological malignancies were found to be use of a central venous catheter and neutropenia for more than 6 days 4. Candidemia is still a serious disease in hematology patients, although the incidence of candidemia has reduced with the introduction of azole drugs in the 1990s 5. The candidemias generally develop endogenously through invasion of the gastrointestinal tract or as a catheter-related infection 6,7.…”
Section: Introductionmentioning
confidence: 99%